(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The study aimed to identify the availability of competencies for designing e-learning experiences for people with disabilities among faculty members in Saudi universities. The study sample included (53) faculty members from the departments of educational technologies and special education in the universities of: Um Al-Qura, King Abdulaziz, Jeddah, and Taif, out of a study community consisting of (200) members. The questionnaire was used to collect data. The results showed that the administrative technical competencies received the highest evaluation, followed by the evaluation competencies, while the design, technical and facilitation competencies were close with averages ranging between (4.15) and .(4.16)While differences appeared in the variable of years of experience in favor of the category (5 to 10 years), and in the academic qualification in favor of the category "PhD". The results also showed statistically significant differences in managerial technical competencies in favor of females compared to males. The study concluded with recommendations that include providing periodic training programs for faculty members, focusing on practical applications and modern technologies in the design of e-learning, to enhance efficiency and ability to meet the needs of people with disabilities.